KESESUAIAN (FIT) ANTARA LINGKUNGAN DENGAN ORIENTASI STRATEGI UNTUK MENINGKATKAN KINERJA USAHA KECIL MENENGAH (UKM): SEBUAH MODEL PENGEMBANGAN TEORITIS - Suliyanto Suliyanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2009)
Research on the orientation of the strategy with the environment have been carried out by previous researchers, but still produces a variety of findings, in addition to the research is generally done in large companies. Therefore, research on strategic orientation fit and environment in small and medium-sized companies that use environmental typology of Dess and Beard, (1984) still needs to be done.